A simple method for generating high-resolution maps of genome-wide protein binding - Skene, Peter J; Henikoff, Steven (eLife, 2015)
Chromatin immunoprecipitation (ChIP) and its derivatives are the main techniques used to determine transcription factor binding sites. However, conventional ChIP with sequencing (ChIP-seq) has problems with poor resolution, and newer techniques require significant experimental alterations and complex bioinformatics. Previously, we have used a new crosslinking ChIP-seq protocol (X-ChIP-seq) to perform high-resolution mapping of RNA Polymerase II (Skene et al., 2014). Here, we build upon this work and compare X-ChIP-seq to existing methodologies. By using micrococcal nuclease, which has both endo- and exo-nuclease activity, to fragment the chromatin and thereby generate precise protein–DNA footprints, high-resolution X-ChIP-seq achieves single base-pair resolution of transcription factor binding. A significant advantage of this protocol is the minimal alteration to the conventional ChIP-seq workflow and simple bioinformatic processing.
Keywords: transcription factor; RNA polymerase II; CTCF